The Relevance of Blood Cell-Vessel Wall Adhesive Interactions for Vascular Thrombotic Disease - May, Andreas E.; Neumann, Franz-Josef; Preissner, Klaus T. (Thrombosis and Haemostasis, 1999)
Following an inflammatory or infectious stimulus, the body’s defense mechanism initiates recruitment of circulating leukocytes toward the inflammatory stimulus. The emigration of leukocytes into extravascular tissues occurs in a highly coordinated fashion in multiple steps, including rolling and tethering of blood cells along the vascular endothelium and their firm attachment and subsequent transmigration and invasion toward the inflammatory site.1 During these sequential steps, transcellular recognition of different adhesion receptor/counterligand pairs, such as selectins/sialyl LewisX-carbohydrates,2 integrins/ immunoglobulin superfamily cell adhesion molecules (ICAMs),3 or binding to (provisional) extracellular matrix components, such as fibrinogen/fibrin, vitronectin, or fibronectin, control the strength and duration of interactions between leukocytes (neutrophils [polymorphonucleocytes (PMN)], eosinophils, monocytes and macrophages, mast cells, lymphocytes) and the vessel wall.4 The importance of these cellular interactions is evident from patients with the rare congenital disorders of “leukocyte-adhesion-deficiency,” which are either caused by a lack or dysfunction of ß2-integrins (LAD I) or a deficiency in the expression of sialyl-LewisX carbohydrates (LAD II).5 The interdependent adhesion processes are regulated by vascular cell-derived chemokines and chemoattractants that may directly influence the expression profile and activation state of adhesion molecules, such as ß2- and ß1-integrins, the shedding of selectins, and the nonthrombogenic properties of endothelial cells.6 Prior to transmigration, leukocyte adhesion may induce the disruption of vascular endothelial (VE)-cadherin mediated endothelial cell-to-cell junctions7 involving the proteasome machinery.8The spatio-temporal cellular expression of juxtacrine adhesion and signaling receptors–particularly on PMN, endothelial cells, and platelets–contribute to the coordination of adhesion and inflammatory mechanisms required for vascular homeostasis9 and prothrombotic outcome under imbalanced conditions. Not only do monocytes express tissue factor (a receptor for the protease factor VII/VIIa) on their surface after stimulation with endotoxin or cytokines, but PMN contain cell surface receptors, such as the factor X/Xa-binding ß2-integrin Mac-1 or effector cell protease receptor (EPR)-1, that link cellular activation and inflammation with the induction of the blood clotting cascade and serve as an alternate pathway for thrombin formation.10,11 Moreover, defects in natural anticoagulant mechanisms, such as the thrombomodulin/protein C pathway, are potential risk factors for vascular thrombotic complications, as in myocardial infarction.12 Pathophysiological stimuli, such as dysregulated direct (i.e., adhesive contact) or indirect (i.e., release of soluble factors) activation of leukocytes, serious infectious agonists, or autoantibodies, may result in endothelial cell dysfunction or injury with the amplification of inflammatory and prothrombotic responses. In the following, some of the principal juxtacrine interactions between leukocytes, platelets, and endothelium, together with their direct or indirect influence on hemostasis and consequences for vascular thrombotic disease, will be discussed. Further understanding of the bidirectional cross-talk of adhesion receptors and the contribution of connecting points, such as protease receptors, may lead to promising therapeutic strategies that aim to protect or regain the endothelial defense mechanisms.